Morphology, Physiology, and Anatomy of Penny Fern (Drymoglossum phyloselloides)and Its Effect on Cocoa - Fitria Yuliasmara; Fitria Ardyani (Indonesian Coffee and Cocoa Research Institute, 2013)
This study aims to determine the anatomy, physiology and morphology of penny fern (Drimoglosum phylloseloides) and its effect on cocoa. Morphological observation of penny fern used microscope to observe the roots, stems, leaves and spores. Physiology of penny fern was observed based on number of stomata and stomatal conductance using stomata printing method, while the amount of chlorophyll based on spectrophotometric method and rate of transpiration used cobalt chloride paper. Penny fern anatomy on cross-sectional and longitudinal in roots, stems and leaves. Penny fern growth was observed based the length of tendrils once a week during rainy and dry season. While the effect of penny fern invasion was observed based on variable leaf area with gravimetric method, the cross-section of attacked cacao branch using microtom and microscope and chlorophyll content by chlorophyll meter. Results showed that penny fern is a epiphytic weed which was crassulaceae acid metabolism plants that have the ability to absorb carbon dioxide at night and carry out photosynthesis during the day with closed stomata. Penny ferns reproduce using spores. The growth rate of penny fern 2.18 cm/week during the dry season and while in rainy season 3.89 cm/week. Penny fern leaf contains 0.0212 mg/g chlorophyll. Penny fern stomata density was 18.33/mm 2 with a width of opening stomata at night 26.3 µm which caused a veryslow rate of transpiration of 0.69 mm 2 /seconds. The existence penny fern on cocoa decreased leaf area and chlorophyll content decreased crop productivity which was indicated by decreasing in number of flowers, number of small, medium fruit, and large pods. However it had no effect on the number of leaves on one side flush cocoa. Key words: Drimoglosum phylloseloides, weeds, decrease productivity, Theobroma cacao